6C.05: STK39 AND WNK1 ARE POTENTIAL HYPERTENSION SUSCEPTIBILITY GENES IN THE BELHYPGEN COHORT. (June 2015) - Persu, A.; Evenepoel, L.; Jin, Y.; Mendola, A.; Staessen, J.A.; Vikkula, M.
Abstract : Objective: The serine threonine kinase WNK1 activates the thiazide-sensitive Na+/Cl- co-transporter in the distal tubule, at least partly through phosphorylation of another serine threonine kinase named SPAK, encoded by the STK39 gene. We looked for a possible association of WNK1 and STK39 genes with blood pressure (BP) and hypertension in Belgium. Design and method: 779 Caucasian hypertensive patients (HYP) recruited in six academic centres from Belgium and 906 normotensive (NT) controls were genotyped for rs3754777 (STK39) and rs1468326 (WNK1) using the Snapshot® methodology. Results: Hypertensive patients were aged 56.9 years, had a mean BMI of 28.3 kg/m2 and systolic BP of 147.9 mmHg on an average of 1.9 drugs. Controls (mean systolic BP: 117 mmHg) were younger (mean age: 36.6 years) and leaner (mean BMI: 23.4 kg/m2). The rare TT genotype at the STK39 locus was overrepresented in HYP vs. NT (7.3 vs. 3.0%, p = 0.0002). In the whole study population, with adjustments applied for sex, age, BMI and the number of antihypertensive drugs, the odds ratio (OR) of having hypertension associated with the TT genotype was 5.9 (CI, 2.2–15.6); the corresponding effect size on a continuous scale was a 10 mmHg higher systolic BP in TT carriers (140.1 vs. 130.4 mmHg in wild type subjects, p = 0.002). Similarly, the AA genotype at the WNK1 locus was twice as frequent in HYP vs. NT (5.5 vs. 2.3%, p < 0.0001), and associated with an increased multivariable-adjusted OR of hypertension (4.1; 1.5–11.7) and a higher systolic BP (139.8 in AA vs. 130.1 mmHg in wild-type, p = 0.003). In the whole cohort, a dose-dependent increase in systolic BP was observed according to the number of at-risk genotypes (0: 129.8 mmHg; 1: 133.0 mmHg; 2: 149.3 mmHg, p = 0.02). Subjects harbouring the risk alleles at the heterozygous state did not differ from wild type for the studied parameters, consistent with a recessive effect at both loci. Conclusions: Our multicentre Belgian case-control study identifies STK39 and WNK1 as potential hypertension susceptibility genes. Replication in different clinical settings and study of other candidate loci belonging to the same metabolic pathway is warranted.